PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 1 TANJUNG MUTIARA - Zeha, Natatise (Jurnal Edukasi dan Penelitian Matematika, 2025)
Developing strong problem-solving skills is the goal of mathematics education. However, in Tanjung Mutiara, this ability in class XI of SMAN 1 is still lacking. Applying one of the Realistic Mathematics Education (RME) approaches is a way that has been implemented. This study used a nonequivalent posttest only control group design. Data analysis indicated that in class XI of SMAN 1 Tanjung Mutiara, learning mathematics is more effective through the RME method compared to the conventional method. If the RME approach is practiced, skill development especially in problem solving will increase.Keywords– Realistic Mathematics Education, Conventional Approach, Problem-Solving Skills